OPTIMISASI PENEMPATAN POSISI ACCESS POINT PADA JARINGAN WI-FI MENGGUNAKAN METODE SIMULATED ANNEALING - , NILA FEBY PUSPITASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Access Point Placement on Wi-Fi networks that are needed to optimize the exact strength of signal received from transmitter to receiver. The most influential parameter in determining performance of access point position is value of signal strength, because this is value that will be used to determine coverage area from a transmitter. This research has been done on measuring signal strength of access point to receiver in the faculty room and the lobby floor 1 of building 2 at STMIK AMIKOM Yogyakarta measured using inSSIDer application and the resulting value of RSSI from transmitter to receiver. Also used in the measurement of LOS propagation and NLOS propagation. Data obtained from the results field measurements are used to perform modeling access point placement using simulated annealing. RSSI signal strength received by the receiver does not only depend on the distance between the transmitter and receiver, but show large variations of the fading and shadowing at a location, also the effect of interference can cause a decrease in the signal (RSSI) received by the receiver. From the research conducted, is expected to generate an appropriate modeling and appropriate in further optimization of access point position on Wi Fi network using simulated annealing.